«Смерть Анны Андреевны Ахматовой — великая потеря» (Из писем Льва Аренса Григорию Петникову) [“Anna Akhmatova’s Death is a Great Loss”: From Lev Ahrens’ Letters to Grigory Petnikov] - Poberezkina, Polina (Slavica Revalensia, 2022)
This article, completed during Dr. Polina Poberezkina’s stay in Estonia, examines several accounts of Anna Akhmatova’s last years and the poet’s funeral. It is centered around some letters of Lev Ahrens to Grigory Petnikov from the Central State Archive-Museum of Literature and Arts (Kyiv, Ukraine) supplemented by letters from Anna Garf and Natalia Briukhanenko to the same addressee.